The Antecedent of Customer Delight and Customer Loyalty and Their Impact on Revisit Intention - Yuliawati Kusumaningrum; Tanggor Sihombing; Ferdi Antonio; Rosdiana Sijabat (Syntax Corporation, 2022)
The purpose of this study was to examine the model of the antecedent of customer delight and customer loyalty and their impact on revisit intention at a Japanese Acupuncture family medicine clinic XYZ, Jakarta. PLS-SEM was used to analyze empirical data obtained through simple random sampling. There were 162 respondents who met the requirements through questionnaire that had been distributed online on March 2021. The result showed that seven of eight hypotheses are supported and one of hypotesis is unsupported. Customer loyalty proven has a postive impact on revisit intention while customer delight could positivly influence customer loyalty. Customer satisfaction, customer trust, persive quality as independent variables found significantly influenced. This research model has predictive accuracy and predictive relevance which are relatively weak against revisit intention. Therefore, it is necessary to develop further research in the future related to healthcare services in acupuncture family medicine clinicsx.